(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
An experiment was conducted at the agriculture research field of Noakhali Science and Technology University, Noakhali-3814, Bangladesh during the period 1st November 2021 to 30 January 2022 to observe the effect of different levels of nitrogen (N) fertilizer on growth and yield of mustard. The experiment comprised four levels of nitrogenous (N) fertilizer viz; control (N0) 0 kg ton ha-1, (N1) 90 kg ton ha-1, (N2) 140 kg t ha-¹, (N3) 190 kg t ha-1. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Application of different levels of nitrogen significantly influenced the Plant height (cm), branches plant-1 (no.), effective siliqua plant-1 (no.), seeds siliqua (no.), 1000-seed weight (g), grain yield (t ha-1), stover yield (t ha-¹), biological yield (t ha-1), harvest index (%) content of mustard. Application of 190 kg ha-1 nitrogen gave the maximum plant height (77.83 cm), Branches plant-1 (5.80), Effective siliqua plant-1 (23.60), Siliqua length (6,17 cm), Seeds siliqua (33.87), 1000-seed weight (3.57 g), grain yield (1.53 t ha-1), Stover yield (3.90 t ha-1), Biological yield (5.43 t ha-1) and the lowest yield was found from control (N0) 0 kg ton ha-1. Consequently, ‘BARI SARISHA-14’ may be suggested to grow for higher yield with N3 treatment. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 99-107